Challenges of coordination in provision of urban infrastructure for new residential areas: the Iranian experience - Yazdani, Saeid; Dola, Kamariah; Azizi, Mohammad Mehdi; Mohd Yusof, Johari (Macrothink Institute, 2015)
Urban infrastructure provides foundations for modern civil community and enhances quality of life. Coordination between different urban infrastructure agencies plays a pivotal role in the success of provision of these critical facilities. In turn, identifying and managing interdependency between different urban infrastructures is a key issue in establishing robust coordination in the process of the provision of urban infrastructure. To this end, the present paper, by reviewing the pertinent literature and investigating the current coordination context of urban infrastructure provision in Iran, provides a conceptual framework for identifying the roots of coordination challenges in this salient domain of urban knowledge. The interdependency between urban infrastructure and complexity of the urban infrastructure provision, two significant features of urban infrastructure provision, are two highlighted points in the framework.